IMPACT OF FINTECH INNOVATION TO TRANSFORM REGIONAL RURAL BANKS (RRBS) IN INDIA-A STUDY WITH SPECIAL REFERENCE TO KARNATAKA. - Basavaraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian banking is incomplete without mentioning the exponential growth in digital banking and technological advancements. India is leveraging fintech innovations to transform Rural Rural Banks (RRBs). As the Government pushes ahead with the "One State, One RRB" policy to consolidate RRBs, fintech companies have a golden opportunity to play a pivotal role in rapidly moving RRBs into the digital age. With widespread penetration in rural areas, RRBs are crucial in driving financial inclusion across the country. However, given the changing dynamics in digital payments and financial services, it is critical for RRBs to modernize and integrate with modern technology based payment ecosystems such as Aadhaar Enabled Payments System (AePS), Unified Payments Interface (UPI), and Unified Lending Interface (ULI). The research paper highlights and examine that the how fintech innovation to transform RRBs in India and examines how the use of FinTech solutions has resulted in financial inclusion and banking services in rural areas. This study also analyses the impact of fintech in the rural banking operations and performance. This study is based both primary data and secondary data. This is in descriptive in Nature. The data will be analyzed through some statistical tools such as percentage,Mean, Kendalls ‘w’test and Chi square test.